The contribution of the accounting information system in supporting the administrative process - a field study for the Naftal Comercial Corporation in M’sila) - benaissi, Moussa; laaraf, Faiza (Journal of Research in Finance and Accounting, 2022)
The study aims to clarify how the accounting information system contributes to supporting and strenthening the administrative process of Naftal Corporation Comercial in M’sila. Thought the basic role of the accounting information system in producing accounting information of quality and delivering it appropriately and at the appropriate time to the different administrative levels for the purpose of performing its basic functions of planning, control and decision-making. This study found that the accounting information system has an important position within Corporation for supporting different management levels by meeting management’s information requirements.